Syariat Islam dalam Perspektif Gender dan Hak Asasi Mansia (HAM) - Mohamad Ikrom (UIN Sunan Kalijaga Yogyakarta, 2013)
This writing background by concern to role and good responsibility (gender)woman in domestic domain as well as public domain that is straight experiencediscrimination, subordinated and violence. Whereas, by normative Al-Qur`an depictsideal figure a woman as private that own autonomy in various fields life, particularlyautonomy in political sphere. However, when the teaching that is ideal and sacred downthrough earth and interact by various culture human, often happened by distortions inthe interpretation. Understanding that distortif appear, because several factors. Amongother things because understanding dogma that very tekstual until ignore thekontekstual aspect, besides because sosio-kultural influence background and sosiohistoris human that interpret him. Because of focus study in this writing is how syariatIslam in perspective gender and HAM. However inferential that, role andresponsibility woman equivalent with man. Both eqully creation God, eqully human,eqully potentially become fi al-ardh caliph and also eqully potentially become fi al-ardhdamage. Man humanity value and same woman, do not have difference even a little.Because task human only ber-fastabiqul something good (vie act best) for expect ridhaAllah SWT.